Solvothermal Syntheses, Crystal Structures, and Luminescent Properties of Two Coordination Polymers with Different Interpenetrated Diamond Topology1. Issue 7 (21st April 2015) - Deng, Xiaoqi
Abstract Two coordination polymers, namely, [Zn(bpea) (bmp)]·H2On (1) and [Ni(bpea)(bimb)]·DMFn (2) [H2bpea = biphenylethene‐4, 4′‐dicarboxylate, bmp = 1, 4‐bis(2‐methylimidazol‐3‐ium‐1‐yl)biphenyl and bimb = 1, 4‐bis(1‐imidazol‐yl)‐2, 5‐dimethyl benzene], were synthesized under solvothermal conditions with mixed organic ligands. Single crystal X‐ray diffraction reveals that complex 1 features a three‐dimensional (3D) structure with a sixfold interpenetrating dia net. Complex 2 shows a 3D fivefold interpenetrating dia topology. Furthermore, the solid state luminescent properties of complexes 1 and 2 were investigated at room temperature.